University of Malaya's emerging scholars leadership advancement (Emerald) programme: Implications on new lecturers' early career development - Firdaus, Amira Sariyati; Abdul Ghaffar, Fauza; Yusop, Farrah Dina; Hamzaid, Nur Azah; Abu Hassan, Zahiruddin Fitri; Yap, Min Chen; Senom, Fatiha; Abu Bakar, Aishah; Ngeow, Yeok Meng; Jamaludin, Ferlynda Fazleen (2017)
Interest on the professional development of an academic in academia has been growing over the years (Akerlind, 2005). Research indicates that there are various academics preparation programmes preparing Early Career Faculty, i.e. young, new and novice academics, for tasks in academia. This study explores the effectiveness of one of the training programme for new lecturers - Emerging Scholars Leadership Advancement (Emerald) programme held by UM's Academic Enhancement and Leadership Development Centre (ADeC) since August 2014. It is a training programme for new academic staffs who have successfully obtained their doctorates via UM's faculty recruitment and training schemes (i.e. Skim Latihan Akademik Bumiputera (SLAB) and Skim Latihan Akademik IPTA (SLAI)). Findings were analysed from three focus group discussions with 12 Emerald participants as well as two stakeholder meetings with their deans and departmental heads. Further post-training in-depth interviews with four alumni from the programme are underway. Earlier findings suggest that although Emerald participants seemed to appreciate the learning opportunities and networking possibilities gained from Emerald, the programme was also burdensome time-wise, and somewhat irrelevant to their daily duties as new faculty. Relevance of some of the programme's components to the daily duties as new faculty were questioned. In addition, the programme's lack of gains in terms of contributing to their efforts toward tenure was also highlighted. It is therefore vital to examine the ECF's reception of the programme, and its perceived benefits and drawbacks in providing relevant training for new lecturers in the early months of their academic career. These findings provide basis for ongoing revisions to the programme, wherein teaching and learning, supervision, and research training modules were reviewed and amended. In addition, changes were made to the programme briefing session as well as its practical attachments modules. Most importantly, the Emerald programme structure underwent modifications cut the programme duration from 60 days to approximately 20 days with training that focused on the core duties of new lecturers. This study contributes to existing efforts to improve the training of ECF by chronicling the development and subsequent ongoing enhancements of the ECF training programme at Malaysia's leading public university.